2011
DOI: 10.1051/0004-6361/201015873
|View full text |Cite
|
Sign up to set email alerts
|

The long-term dynamics of the Jovian irregular satellites

Abstract: Context. The dynamical region of the Jovian irregular satellites presents an interesting web of resonances that are not yet fully understood. Of particular interest is the influence of the resonances on the stochasticity of the individual orbits of the satellites, as well as on the long-term chaotic diffusion of the different families of satellites. Aims. We make a systematic numerical study of the satellite region to determine the important resonances for the dynamics, to search for the chaotic zones, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…region X in Fig. 2) (this is similar to the behavior of many Solar System irregular satellites: (Nesvorný et al 2003;Frouard et al 2010Frouard et al , 2011, and references therein).…”
Section: Prograde 2-planet 1-satellitesupporting
confidence: 75%
“…region X in Fig. 2) (this is similar to the behavior of many Solar System irregular satellites: (Nesvorný et al 2003;Frouard et al 2010Frouard et al , 2011, and references therein).…”
Section: Prograde 2-planet 1-satellitesupporting
confidence: 75%
“…In Christou (2005), Saturn and the jovian oblateness were taken into account and in such a configuration, he found the resonance in ∆ Ω . Including other planets may introduce additional dynamical effects such as secular resonances (see, e.g., Beaugé and Nesvorný 2007;Frouard et al 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Hinse et al (2010) applied the MEGNO technique to jovian irregular satellites and identified chaotic and quasi-periodic regions; they also found some high-order mean motion resonances. Using similar methods, Frouard et al (2011) reported a number of resonances related to the Great Inequality and revealed the chaotic diffusion in different irregular satellite groups.…”
mentioning
confidence: 99%
“…We used the MEGNO indicator (Cincotta & Simó 2000) in order to distinguish among regular and chaotic orbit. The MEGNO is a fast chaos indicator based on the numerical integration of a tangent vector, that has proved to be reliable in a large class of dynamical systems (Cincotta et al 2003;Goździewski et al 2001Goździewski et al , 2008aBreiter et al 2005;Compère et al 2012a;Frouard et al 2011).…”
Section: Short-term Numerical Integrationsmentioning
confidence: 99%